SYNTHESIS OF 5-(2-THIENYL)-4,5-DIHYDROFURA NS AND 7-(2-THIENYL)-2,8-DIOXABICYCLO[3.3.0]OCT-3-ENES USING MANGANESE(III)-BASED CYCLIZATION - Huỳnh Thanh Trúc; Nguyễn Văn Hạ (Tạp chí Khoa học Đại học Đà Lạt)
1-Aryl-1-(2-thienyl)ethenes react with 2,4-pentanedione or ethylacetoacetate in boiling acetic acid under the presence of manganese triacetate dihydrate affording new 4,5-dihydrofurans bearing a thienyl ring at the 5 position. On the other hand, these ethenes react with 3-acetyl-1-phenylpentane-1,4-dione in a similar reaction leading to the formation of 7-(2-thienyl)-2,8-dioxabicyclo[3.3.0]oct-3-enes in high yields. The cis manner of fused bicyclic products is briefly discussed.